**More Articles**

Cold War Era – When peoples suffer the war

If the roots of the equation (a-b)x^2 +(b-c)x+(c-a) =0 then prove that b+c=2a

Facebook Comments

Please follow and like us:

Skip to content
# tan theta – cot theta/sin theta cos theta = tan^2 theta – cot^2 theta.

Learn, Educate and Grow

**More Articles**

Cold War Era – When peoples suffer the war

If the roots of the equation (a-b)x^2 +(b-c)x+(c-a) =0 then prove that b+c=2a

Facebook Comments

Please follow and like us:

Don`t copy text!